Communication and Conflict Management - Gerald Eisenkopf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper studies an experimental conflict in a repeated game and tests the robustness of communication as an intermediate conflict resolution instrument. The results show a strong and persistent impact of communication. Most conflict parties refrain from conflict expenditures even after the opportunity for communication has expired. Third party involvement with punishment options do not enhance this effect while the indivisibility of the contest prize reduces it. The initial intensity of the conflict has a small but long-term negative impact on conflict resolution.
Keywords: C92; F51; D74; 330